GENETIC VARIATION IN TWO SPECIES OF FRUIT FLIES OF THE GENUS BACTROCERA (DACINAE: TEPHRITIDAE: DIPTERA) - RASHMI SINGH; AKANKSHA SINGH (International Journal of Pharma and Bio Sciences, 2013)
Multilocus enzyme electrophoresis data from 14 orthologous loci (25 alleles) were used to infer the genetic variation between the two Tephritidae species, Bactrocera (Dacus) cucurbitae and B. (D.) dorsalis, which are common pests of vegetables and fruits in India. Out of fourteen loci analyzed, seven loci were polymorphic in B. cucurbitae and nine loci were polymorphic in B. dorsalis. The amount of observed (0.18) and expected heterozygosity (0.26) in B. cucurbitae were lower than the observed (0.33) and expected heterozygosity (0.40), in B. dorsalis. The estimates of genetic variation in terms of observed and expected heterozygosity were higher as compared to the general low level of variability found in tephritid fruit flies. Nei’s genetic identity value (0.833) reveals a very close genetic similarity between the two species.